Better animals, more jobs - Rudiger, Udo; Ekule, Muluken (ICARDA, 2024)
In 2022, ICARDA collaborated with a Community of Practice (CoP) to train a group of 150 farmers, mainly youth and women, about the importance of livestock nutrition and the value of feed components. In 2023, ICARDA distributed three locally manufactured feed processing machines, which included a grinder, conveyor, and feed mixer, to sheep-fattening youth groups in Bassona Werena (North Shewa), Boka-shut (Bonga), and Serara (Doyogena) in Ethiopia. The machines meant these groups could now produce and sell compound feed concentrates to their members and neighbouring farmers